Effect of Concentration of Liquid Organic Fertilizer and Arbuscular Mycorrhizal Fungi (CMA) on Growth and Red Bean Plant (Phaseolus vulgaris L) - Nurfitri, Mesy; Jaenudin, Amran; Nur, Subandi (Ann Publisher, 2024)
This study aims to determine the interaction between the effect of liquid organic fertilizer concentration and arbuscular mycorrhizal fungi (CMA) on the growth and yield of red bean plants (Phaseolus vulgaris L.). The experiment was conducted in Nusaherang Village, Nusaherang District, Kuningan Regency, from July to September 2022. The research method used is the experimental method of Group Random Design (RAK) factorial pattern. The treatment consists of two factors and is repeated three times. The first factor is the concentration of liquid organic fertilizer (P), which consists of three levels, namely: P1 (5 ml / l), P2 (10 ml / l), and P3 (15 ml / l). The second factor of arbuscular mycorrhizal fungi (C) consists of three levels, namely: C1 (5 g / plant), C2 (10 g / plant), and C3 (15 g / plant). The primary observation data is processed using variance analysis; if there is a noticeable effect, the test is continued with the Duncan multiple distance test. The results showed a real interaction between the concentration of liquid organic fertilizer and arbuscular mycorrhizal fungi on plant height aged 21 HST, root length aged 21 HST, number of flowers aged 35 HST, and number of pods per red bean plant. The concentration treatment of liquid organic fertilizer has an independent effect on the number of leaves aged 21 HST. In comparison, the treatment of arbuscular mycorrhizal fungi has an independent effect on the number of leaves aged 21 and 28 HST and the number of seeds per pod. The treatment of liquid organic fertilizer and arbuscular mycorrhizal fungi has the same effect on yield variables, so the average weight of fresh red bean beans per plot is 626 g (0.63 kg) or equivalent to 1.6 tons/ha, assuming 80% of the land is effective.